Study of cardiovascular manifestations in treatment naive HIV patients and patients on HAART and its correlation with CD4+ cell counts in a tertiary care centre - Siddaraju, Meghana Belagula; G., Madhu; R., Madhumati; Gowda, Shilpa Tumkur Andane (International Journal of Advances in Medicine, 2020)
Background: Highly active anti-retroviral therapy (HAART) increases the longevity of the patients infected with Human immunodeficiency virus (HIV) so mortality due to opportunistic infections is reducing and late complications like cardiovascular manifestations are on its rise. Cardiac involvement can be over-looked in HIV positive patients because symptoms of breathlessness, fatigue and poor exercise tolerance are ascribed to other conditions associated with HIV patients. Objective: Primary objective was to evaluate cardiac manifestations and determine type of cardiac involvement in both HAART naïve patients and patients on HAART and correlate with CD4+ counts. Methods: 200 HIV infected patients presenting in outpatient department (OPD) and inpatients are included. Information is collected and detailed history is taken using pre-formed proforma. At the time of admission or follow up, steps are taken to send for all the investigations and detailed clinical examination of the patient done, focusing more on cardiovascular system. Results: 41% of the patients with normal cardiac function were not on HAART and 62.7% of the patients with cardiac dysfunction were HIV naïve and it was found to be statistically significant (p value 0.003). Tricuspid regurgitation (42.1% verus 57.9%, p value 0.035) and Ischemic heart disease (IHD) (0% versus 100% p value 0.049) found to have significant association in patients who were on HAART. Systolic dysfunction (p value 0.048) and IHD (p value 0.019) were both significantly associated with the low CD4+ counts in patients not on HAART. Conclusion: There was significant association of HAART on the occurrence of cardiac dysfunction. Cardiac dysfunction is noted with low CD4+ counts, it is therefore important to undergo 2-dimensional echocardiography (2-D Echo) at diagnosis and at regular intervals in all HIV infected patients and to initiate early treatment for the same.the rural population.